The Relationship Between Knee Osteoarthritis and Osteoporosis in Postmenopausal Women - S. Karakaşlı; H. Uğurlu; O. Tüfekçi; F. Levendoğlu (Türk Osteoporoz Dergisi)
In this study the bone density of the upper femur and radius were compared accoding to the severity of knee osteoarthritis (OA), bone mineral index (BMI) and age. Eighty two postmenopausal women with knee osteoarthritis were recruited in this study. Bone mineral density of the femur and radius was measured using dual energy x-ray absorptiometry(DEXA). Radiological grading of knee OA was done by using Kellgren-Lawrence and individual feature scales. In our study, there were 15 subjects with Kellgren and Lawrence grade 0, 13 with grade 1, 21 with grade 2, 25 with grade 3, and 8 with grade 4 OA. There were no differences in hip and radius bone mineral density (BMD) by presence of any radiographic features of OA in patients (p>0.05). BMD of the femoral neck and trochanter was significantly associated with BMI (p<0.01). Negative correlation was found between age and BMD (p<0.05). BMD was not associated with knee OA. With aging, we found a strong correlation between the femur BMD and BMI, although BMD decreased with age.